2019
DOI: 10.1002/path.5366
|View full text |Cite
|
Sign up to set email alerts
|

Proteome analysis of formalin‐fixed paraffin‐embedded colorectal adenomas reveals the heterogeneous nature of traditional serrated adenomas compared to other colorectal adenomas

Abstract: Traditional serrated adenoma (TSA) remains the least understood of all the colorectal adenomas, although these lesions have been associated with a significant cancer risk, twice that of the conventional adenoma (CAD) and of the sessile serrated adenoma (SSA/P). This study was performed to investigate the proteomic profiles of the different colorectal adenomas to better understand the pathogenesis of TSA. We performed a global quantitative proteome analysis using the label‐free quantification (LFQ) method on 44… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…While the latter can be problematic in large series 56 they reported high identification numbers for their FFPE samples comparable to FF samples 57 . These were collected prospectively under study conditions, presumably with standardized short fixation times, explaining the difference to our and others’ identification numbers with archival FFPE tissue 44 46 , 58 . Based on proteins expressed in 30% of all samples and with a dominance of MIBC samples (n = 71; 61%) they identified three proteomic clusters with significant survival stratification in univariate analysis (ibid.…”
Section: Discussionmentioning
confidence: 72%
“…While the latter can be problematic in large series 56 they reported high identification numbers for their FFPE samples comparable to FF samples 57 . These were collected prospectively under study conditions, presumably with standardized short fixation times, explaining the difference to our and others’ identification numbers with archival FFPE tissue 44 46 , 58 . Based on proteins expressed in 30% of all samples and with a dominance of MIBC samples (n = 71; 61%) they identified three proteomic clusters with significant survival stratification in univariate analysis (ibid.…”
Section: Discussionmentioning
confidence: 72%
“…investigating the proteomic effects in the liver with knock down of a central metabolic enzyme (dC1; PXD002025; ebi.ac.uk/pride) [30] and a study in human tissue by Sohier et al, in which distinct pathological types of colorectal adenoma were compared on proteome level (dC2; PXD014511; proteomecentral.proteomexchange.org) [31].…”
Section: Complex Datasetsmentioning
confidence: 99%
“…Specific biomarkers for the differential diagnosis of TSAs have not been established. However, Sohier et al [73] performed proteomic analysis using formalin-fixed, paraffin-embedded tissues of various types of serrated lesions and conventional adenomas and found that LEFTY1, an inhibitory protein of the Nodal/transforming growth factor β pathway, was overexpressed specifically in TSAs. Although this may be promising, more studies will be necessary to validate whether LEFTY1 immunohistochemistry is practically useful in the diagnosis of TSAs.…”
Section: Molecular Pathogenesis Of Tsasmentioning
confidence: 99%
“…Third, immunohistochemical or molecular biomarkers should be further developed and validated to aid in the differential diagnosis or prognostic subgrouping of serrated colorectal lesions. Recently studied proteins such as AGRN and LEFTY1 are potential biomarkers which can aid in the differential diagnosis of serrated lesions [62,73].…”
Section: Future Directionsmentioning
confidence: 99%